Development and Characterisation of Yoghurt incorporated with Dates (Phoenix Dactylifera Linn) Extract - S, Archana; K B, Divya; SN, Rajakumar; P, Sudheerbabu (Indian Journal of Dairy Science, 2023)
Nowadays, functional dairy products gain more acceptance in the market because of the additional health and nutritional benefits they provide to the consumer. Value addition of dairy products like yoghurt often augments the market value as well as functionality of the product. Dates (Phoenix dactylifera Linn) are natural source of phytochemicals like phenolic acids and flavonoids which are proved to have strong anti-oxidant activity. In this study, the effect of addition of dates extract into yoghurt milk was studied. Hot water extract of dates fruit was added to the yoghurt at different levels (30%, 32%, 34%, and 36%) and the optimum level of addition was selected on the basis of sensory scores obtained from 5 semi trained judges. Significant differences (p<0.01) were found in the sensory scores of different treatments and the overall highest score was obtained for yoghurt with 34% dates extract. The product selected was subjected for physico chemical analysis and the findings were: fat 2.85%, protein 3.8, total solids 15.88 and acidity 0.79% Lactic acid (LA). The total phenolic content of the product was measured in terms of milligrams of Gallic acid equivalents (GAEs) per 100 grams of sample (mg GAE/g of sample) and was found to be 59 mg GAE/100g. The phenolic contents in the product was proved to impart antioxidant activity in the yoghurt as the IC 50 value; the half maximal inhibitory value, was found to be 19.99mg/mL of the sample.